An alternative experimental methodology to determine the diagonal cracking resistance of steel-reinforced concrete beams. (1st October 2021) - Romera, Jesús M.; Marcos, Ignacio; Skaf, Marta; Ortega-López, Vanesa
Highlights: A new approach is presented for determining the diagonal cracking resistance. The method is not dependent on the subjective visual appraisals of the cracks. The results are obtained by using conventional measuring instrumentation. Concrete mixes containing EAF steel slag aggregates have been assessed. Abstract: An alternative experimental method for predicting the diagonal shear cracking resistance of steel-reinforced concrete beams is developed in this paper. Conventional extensometric strain-gauge rosettes are placed on the lateral surfaces of a set of four beams. As diagonal cracking propagates through the beams, the load–strain curves flatten out at a plateau and the mechanical property under consideration may be determined. The method is applied to four beams cast from pumpable and self-compacting concrete mixes with cement types I and IV containing electric arc furnace slag aggregates. The feasibility of applying standard design code formulas to the concretes containing these aggregates may therefore be studied and compared with other recent research works. Accurate experimental results were obtained with this method without having to interrupt the test for subjective visual appraisals of the test specimen.